Auditoría de gestión y su relación con la optimización de los servicios de la unidad educativa San Camilo, cantón Quevedo, año 2014 - Ayala Pérez, Katherine Yajaira (2015)
This research is conducting a management audit and its relationship with the optimization of the services of the Education Unit San Camilo, Canton Quevedo, 2014, is located in the parish of the same name, on Avenida Jose Joaquin de Olmedo between the streets "P" and "O". Which was assessing compliance, policies and procedures, aiming at obtaining information on the structural organization, carrying out the activities and services provided as an educational institution. Whereby it has done extensive research using the methods; inductive, qualitative - quantitative and deductive hypothetical, complemented with techniques that leads to knowledge of the efficiency and effectiveness of the Education Unit. The same which is made up of 6 people in administration, 40 teachers and 995 students dedicated to developing the needs of the different activities. According to interviews and surveys actual data could be obtained where the weaknesses could be identified with each of the components of internal control questionnaire. The conclusions of the research work has reflected an inadequate provision of service as Low risk level to 30%, which affects the functions and competence of each of the areas, it involved the failure of activities, getting little employment in the institution, was also identified that the evaluation of the Strategic Plan of the Education Unit does not perform a check on compliance with processes having as risk level under 30% and objectives Under a risk level of 42.86 %, according to law enforcement results in poor training with a risk level below 20% and delay in communicating new changes with a risk level under 40%.